Recruiting policies of 2016 of an educational institution and the impacts focusing on Kurmitola High School and College - Nahar, Kamrun (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.